2007
DOI: 10.1038/nsmb1250
|View full text |Cite
|
Sign up to set email alerts
|

The multifunctional RNA-binding protein hnRNP A1 is required for processing of miR-18a

Abstract: hnRNP A1 is an RNA-binding protein involved in various aspects of RNA processing. Use of an in vivo cross-linking and immunoprecipitation protocol to find hnRNP A1 RNA targets resulted in the identification of a microRNA (miRNA) precursor, pre-miR-18a. This microRNA is expressed as part of a cluster of intronic RNAs, including miR-17, miR-18a, miR-19a, miR-20a, miR-19b-1 and miR-92, and potentially acts as an oncogene. Here we show that hnRNP A1 binds specifically to the primary RNA sequence pri-miR-18a before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
443
2
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 500 publications
(474 citation statements)
references
References 41 publications
21
443
2
8
Order By: Relevance
“…Although the exact mechanism remains to be explored, one possibility is that B23, hnRNPU and hnRNPA1 may influence the RNA processing machinery and trigger cells to undertake a yet uncharacterized B23 acts as a nucleolar stress sensor and promotes cell survival Z Yao et al nuclear apoptotic signaling other than caspase-involved apoptotic pathway in response to nucleolar stress. An interesting work reported recently by Guil and Caceres showed that hnRNPA1 could specifically bind to human pri-miR-18a, a component of the polycistronic miR-17-92 cluster, and facilitate its processing by Drosha, suggesting a potential link between hnRNPA1 and miRNA processing (Guil and Caceres, 2007). Our preliminary data showed that the interaction between B23 and hnRNPA1 was able to affect hnRNA1-mediated processing of the miR-18a precursor (Supplementary Figure S6), and whether the B23/hnRNPU/ hnRNPA1 complex-mediated cell survival is due to regulating miR-18a through B23-hnRNA1-hnRNU interaction is currently being investigated.…”
Section: Discussionmentioning
confidence: 94%
“…Although the exact mechanism remains to be explored, one possibility is that B23, hnRNPU and hnRNPA1 may influence the RNA processing machinery and trigger cells to undertake a yet uncharacterized B23 acts as a nucleolar stress sensor and promotes cell survival Z Yao et al nuclear apoptotic signaling other than caspase-involved apoptotic pathway in response to nucleolar stress. An interesting work reported recently by Guil and Caceres showed that hnRNPA1 could specifically bind to human pri-miR-18a, a component of the polycistronic miR-17-92 cluster, and facilitate its processing by Drosha, suggesting a potential link between hnRNPA1 and miRNA processing (Guil and Caceres, 2007). Our preliminary data showed that the interaction between B23 and hnRNPA1 was able to affect hnRNA1-mediated processing of the miR-18a precursor (Supplementary Figure S6), and whether the B23/hnRNPU/ hnRNPA1 complex-mediated cell survival is due to regulating miR-18a through B23-hnRNA1-hnRNU interaction is currently being investigated.…”
Section: Discussionmentioning
confidence: 94%
“…The abundance of the six miRNAs correlate relatively well except for miR-18a, whose processing has been shown to be regulated by binding of hnRNPA1 to its conserved terminal loop. 32,42 In particular, the abundance of miR-18a is strikingly low in naive B cells. A study of miR-17-92 during mouse development also showed that expression of the individual miRNAs of the cluster did not vary entirely in parallel, 34 with miR-18a showing a disproportionate decrease in several postnatal tissues compared with the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…An additional recently discovered activity of hnRNP A1 is in microRNA (miRNA) biogenesis. A1 was shown to promote processing of miRNA-18a, a miRNA frequently overexpressed in cancer (Guil and Caceres 2007;Motoyama et al 2009). In light of its newfound role in regulating expression of miRNAs, it will be interesting to see if changes in hnRNP A1 expression are responsible for some of the large-scale changes in miRNA expression observed in cancer.…”
Section: Hnrnp and Sr Proteins In Proliferation And Cancermentioning
confidence: 99%